Development of a gravimetric geoid for New Zealand and a single national vertical datum - Amos, Matthew; Featherstone, Will (Ziti Editions, 2003)
New Zealand, unlike most countries, does not have a single national vertical datum. Instead, twelve separate and poorly linked primary levelling networks tied to twelve different tide gauges are used. The current vertical datums are based on the false assumption that mean sea level, measured at the twelve tide gauges, corresponds to an equipotential surface. Due to the effects of long-period tides and sea surface topography, offsets of up to 0.5 metres between vertical datums are possi-ble. In addition, no regional geoid model is available for New Zealand. A consequence of the multiple vertical datums is that the gravity observations are downward continued to twelve different surfaces. This will cause the anomalies to be distorted, especially in the medium wavelengths, which will propagate into the geoid solution, meaning that the initial solution will not completely unify the datums. An iterative process to achieve a better unification is proposed. It is expected that this approach will be more successful than using a geoid model based on distorted gravity anomalies. The results of a regional gravimetric geoid computation using land based gravity observations, satellite altimetry and a global geopotential model are also presented.